La prostitution au Tonkin colonial, entre races et genres - Isabelle Tracol-Huynh (Genre, Sexualité et Société)
War is omnipresent in the historiography of Vietnam and the social aspect of colonization remains neglected. This paper’s aim is to focus on the social and sexual dimensions of French colonization in Northern Vietnam by analyzing colonial prostitution. Prostitution can very well epitomize the parallel and mutual construction of colonial categories (colonizers and colonized, men and women) within a very specific time and space frame. Colonial domination was obviously a matter of racial issues, but gender was at stake too, as the colonizers were not only white but male. Gender and race are then particularly operative concepts when it comes to analyzing this particular phenomenon: prostitution in a French colony, namely Tonkin.